Study on Rheology Properties, Durability and Microstructure of UHPSCC Contains Garnet, Basalt, and Pozzolan - Alireza Rashno; Mohamadreza Adlparvar; Mohsen Izadinia (Journal of Rehabilitation in Civil Engineering)
This study evaluates the rheology and mechanical properties and durability of concrete, which at the same time has properties of three types of self-compacting concrete (SCC), fiber-reinforced and ultra-high performance. This concrete contains pozzolans, garnet and basalt aggregates, and steel fiber. The purpose of this research is feasibility construction fiber-reinforced ultra-high performance self-compacting concrete (UHPSCC) of durable. Therefore, the required tests on this concrete have been carried out in two steps. The first step is the importance of rheology properties of self-compacting concrete, containing the tests of fresh concrete including slump flow, V-funnel test, and L-box test. The second step involves tests related to the determination of hardened concrete properties divided into two parts. The first part corresponds to the mechanical properties test, including compressive strength, and the second part pertains to durability tests (surface water absorption, surface electrical resistivity and RCMT) and microstructural test, including Scanning Electron Microscopy. The above tests show that this type of concrete has rheology properties in the acceptable range EFNARC, ultra-high compressive strength, negligible surface water absorption, minimal chlorine ion migration coefficient, and very high-level electrical resistance has this type of concrete in the ultra-high concrete cluster.